(untitled) (Asian-Australasian Journal of Bioscience and Biotechnology, 2020)
In vitro maturation (IVM) of oocytes provide an excellent opportunity for cheap and abundant embryos for carrying out animal improvement. With the aim for studying the quality of oocyte in different seasons of Black Bengal goat, both right and left ovaries were collected from the slaughter houses. For each of the specimens, gross parameters such as right, left, corpus luteum (CL)-present and corpus luteum (CL)-absent group were evaluated on the basis of weight (g), length (cm), width (cm), follicles aspirated and number and state of cumulus-oocyte-complexes (COCs), normal COCs and abnormal COCs, the effect of season on cumulus oocyte complexes (COCs) of goat oocytes. Our study revealed that the average number of follicles and oocytes recovery rate were higher in summer than in winter season and recovery rate of grade A and B oocytes were higher in summer than that of in winter and recovery rate of grade C and D were higher in winter than that of in summer. In the present study a significantly greater number of oocytes per ovary were recovered from ovaries without a corpus luteum than from ovaries with a corpus luteum. So the summer was the best season for recovery of COCs which have a worthy competence to be matured in vitro. Asian Australas. J. Biosci. Biotechnol. 2020, 5 (3), 78-87